Innovative Discharge Process for Families with Pediatric Short Bowel Syndrome: A Prospective Nonrandomized Trial. Issue 8 (30th March 2018) - Raphael, Bram P.; Jorina, Maria; Gallotto, Mary; Grullon, Glendalis; Dalton, Meghan; Takvorian‐Bené, Melissa; Tascione, Christina; Rosa, Carolyn; McClelland, Jennifer; Gray, Megan; Potemkin, Alexis K.; Glavin, Courtney; et al.
Abstract: Background: Home parenteral nutrition (HPN) is a life‐sustaining therapy for short bowel syndrome (SBS) and other severe digestive diseases, but complications are common. We evaluated a predischarge HPN hands‐on training course to reduce complications in children with SBS, including hospital readmissions. Methods: We conducted a prospective, nonrandomized controlled research study between April 1, 2014, and April 30, 2017. Eligible participants were children aged <18 years old with SBS and anticipated HPN dependence duration ≥6 months. Excluded participants had a previous history of discharge with a central venous catheter (CVC), HPN, or intravenous fluids or strictly palliative goals of care. An intervention group practiced hands‐on HPN within the hospital room for 24 hours using infusion equipment. The groups received standard teaching (CVC care, home infusion pump operation, HPN preparation and administration). Results: Nine children were assigned to the intervention group and 12 served as controls. The median age was 8.4 months, and length of stay (LOS) was 82 days. All participants experienced ≥1 event, with a total of 47 issues related to HPN. There were no significant associations between group assignment and 30‐day postdischarge events. Each additional week of LOS was associated with 11% increase in the odds of an emergency department visit (OR 1.11; 95% CI, 1.01‐1.26) and 16% increase in the odds of readmission (OR 1.16; 95% CI, 1.04‐1.37). Conclusions: Postdischarge events remained widespread despite HPN bedside interventions offered by this pilot intervention. With refinement of HPN discharge processes, quality benchmarks are needed.